Pengendalian Jalan Di Lingkungan Permukiman Perkotaan (Studi Kasus: Perumnas Sadang Serang Bandung) - Setiawan, Altim (SMARTek, 2006)
This article discusses the utilizing of street as public space. Starting from the conflict on the street usage and progressively lack of space for public activities due to the motor vehicle domination and also activity on street as public space in rural settlement environment.Â A normative approach through literature study was conducted to obtain normative control criteria about utilizing street as public space. And also descriptive methodology with existed data collecting technique through field observation and interview had been adopted. Obtained data were in the form of physical and non physical data of study area which were then become reference for further analysis. Result of this study was recommendation in the form of general criteria and guideline that give explanation and instruction of street operation control in the urban settlement environment in Perumnas Sadang Serang.